Pectinolytic yeasts from cold environments: novel findings of Guehomyces pullulans, Cystofilobasidium infirmominiatum and Cryptococcus adeliensis producing pectinases - Cavello, Ivana Alejandra; Albanesi, Agustin Pedro; Fratebianchi de la Parra, Dante; Garmedia, Gabriela; Vero, Silvana; Cavalitto, Sebastian Fernando (Extremophiles)
One hundred and three yeasts isolated from soil samples from King George Island and Tierra del Fuego province were screened in relation with their capability to produce pectinolytic enzymes. Although all the yeasts showed well-developed colonies at 20 °C, only eight showed a clear halo around the colony, indicative of pectin degradation. A secondary screening demonstrated that only four yeasts were capable to produce pectinases at low temperatures (8 °C). It could be seen that the selected yeasts were able to grow and produce high levels of polygalacturonase activity when submerged fermentations were performed using pectin-containing fruit wastes as substrates. None of the strains produced neither lyase nor rhamnogalacturonan hydrolase activities. Regarding pectin esterase activity, it was only produced in lower amounts by G. pullulans 8E (0.022 U ml−1). A TLC analysis of the substrate cleavage pattern of the pectinolytic systems was consistent with an endo-type activity. The clarification of apple juice was only accomplished by G. pullulans pectinolytic system, with a clarification of 80% (%T650) using 4 U/ml of enzyme at 20 °C. As far as we concern this work describes for the first time the production of pectinases by the cold-adapted yeasts species Cystofilobasidium infirmominiatum, Cryptococcus adeliensis and G. pullulans. Fil: Cavello, Ivana Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Universidad Nacional de la Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Fermentaciones Industriales; Argentina Fil: Albanesi, Agustin Pedro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Universidad Nacional de la Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Fermentaciones Industriales; ...